Self-management of lower limb lymphedema at home following gynecologic cancer surgery: a qualitative study of women’s experiences and challenges - Tan, Yuting; Yu, Cong; Mo, Xiuzhen; Sun, Chenghua; Gao, Huina; Song, Shufen; Zhao, Qian (Frontiers in Psychology, 2026)
IntroductionAs a common chronic complication after gynecological cancer surgery, lower limb lymphedema significantly compromises patients’ quality of life, both physically and psychologically. However, patients’ adherence to home-based CDT, the internationally recommended first-line treatment, was frequently inadequate. This study aimed to explore the lived experiences and core challenges faced by women managing lower limb lymphedema at home after gynecologic cancer surgery. The insights gained can guide the formulation of improved nursing care strategies.MethodsA descriptive phenomenological design was employed in this study. Semi-structured, in-depth interviews were carried out with participants managing lower limb lymphedema at home after gynecologic cancer surgery. The collected data were analyzed using Colaizzi’s seven-step phenomenological framework. NVivo version 12.0 software was utilized to facilitate the systematic management of the interview transcripts, supporting a rigorous process of coding and thematic extraction.ResultsThe final study sample included 10 patients aged from 35 to 75 years. Node integration and refinement led to the construction of a thematic structure comprising 4 parent nodes and 17 child nodes. These 4 central themes about patients’ lived experiences and challenges were elaborated as follows: (1) the burden of illness and psychological adaptation struggles, (2) the knowledge-practice gap in self-care, (3) limitations in social and systemic support networks, and (4) the critical demand for professional nursing support.DiscussionThe process of home-based self-management among patients with lower limb lymphedema after gynecological cancer is complex and influenced by multiple factors, which including physiological, psychological, and social dimensions. Current nursing support systems remain insufficient to meet their actual needs. It is recommended to develop a multi-level intervention model, strengthen family-community-hospital collaborative care mechanisms, and promote digital health tools to enhance patients’ self-management capabilities and quality of life.